PENDAFTARAN TANAH DAN KEDUDUKAN SERTIFIKAT TANAH BAGI MASYARAKAT DESA - Vivin Astharyna Harysart; Teguh Endi Widodo; Sulistyani Eka Lestari; Nur Aziz; Marwan Marwan; Dariyuti Dariyuti; Nuris Pratama Wisesa (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2026)
This community service activity aims to increase public awareness regarding the importance of land registration and the legal position of land certificates in rural communities. The background of this activity is the low level of understanding among villagers regarding land registration procedures, legal certainty, and the benefits of land certification. The method used is a participatory and descriptive approach through legal counseling and socialization conducted at Tegalagung Village, Tuban Regency. The results show that the activity was successfully attended by all invited participants (100%), and there was an increase in participants' understanding by approximately 75%. Participants became more aware of the importance of land registration for legal protection, dispute prevention, and administrative order. The activity also encouraged a change in mindset among participants regarding the significance of land certificates.